Internet and Distributed Computing Systems: 6th International Conference, IDCS 2013, Hangzhou, China, October 28-30, 2013, Proceedings - Pathan, Mukaddim; Wei, Guiyi; Fortino, Giancarlo (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 6th International Conference on Internet and Distributed Computing Systems, IDCS 2013, held in Hangzhou, China, in October 2013. The 20 revised full papers and 13 invited papers presented were carefully reviewed and selected from numerous submissions. The papers cover the following topics: ad-hoc and sensor networks, internet and Web technologies, network operations and management, information infrastructure; resilience, as well as fault tolerance and availability.